The Socio-Economic Impact of Covid-19 on The Economic Activities of Selected States in Nigeria - Success Esomchi Obi; Tijani Yunusa; Annе Nnеnna Еzеoguеri-Oyеwolе; Sheneni Samuel Sekpe; Ejura Egwemi; Amina Shaibu Isiaka (CV. Literasi Indonesia, 2020)
COVID-19 pandemic which has spread to 35 states in Nigeria as a health crisis has translated to economic crisis affecting all sector of the Nigeria economy and brought the whole states to its knees. The fundamental question that comes to mind is; in what way did a health crisis translate to an economic crisis? How /why COVID-19 crippled many states economy in Nigeria? Our objective was to examine the socio-economic effect of the lockdown policy on business, transport and service/hospitality industries in three selected metropolis from three states within the period of relaxation. Using the multistage sampling method, we selected 300 respondents across the three sector examined. Data obtained via structured questionnaires was analyzed using inferential statistics. This includes Multiple Regression Analysis, Coefficient for correlations of independent sample and analysis of variance (ANOVA) for significant impact samples. The findings reveal that the increasing number of lockdown days, interstate travel ban, social distancing, and restriction to essentials services severely affected the level of economic activities within the period under review. In contrast, CPL PSL RSM had negative relationship but significant impact in the model, while BSK and ITR negative non-significant impact in the models due to imposed restriction on internal movement, while the rest variables had positive significant effect on the level of economic activities.